2002
DOI: 10.1023/a:1013711314870
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Endometriosis is a condition in which uterine mucosal tissue is located outside the uterus. Endometriosis may be pelvic or extrapelvic. The term endometrioma is used when endometriosis appears as a circumscribed mass. Abdominal wall endometriomas are usually a secondary process in scars after surgical procedures. A retrospective study of abdominal wall endometrioma, from March 1992 through April 1999 at our institution was done. The mean age of the patients was 28.4 years. Twelve of these reported cases were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Minaglia et al who analyzed 30 years of incisional endometriosis after caesarean section found the incidence of scar endometriosis to be 0.08% [4]. Ectopic pregnancies, salpingostomy puerperal sterilization, laparoscopy, amniocentesis, appendectomy, episiotomy, vaginal hysterectomies, and hernia repair are the other surgical factors for scar endometriosis [5–7]. The reported incidence after midtrimester abortion is about 1% also after cesarean sections ranging from 0.03% to 0.45% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Minaglia et al who analyzed 30 years of incisional endometriosis after caesarean section found the incidence of scar endometriosis to be 0.08% [4]. Ectopic pregnancies, salpingostomy puerperal sterilization, laparoscopy, amniocentesis, appendectomy, episiotomy, vaginal hysterectomies, and hernia repair are the other surgical factors for scar endometriosis [5–7]. The reported incidence after midtrimester abortion is about 1% also after cesarean sections ranging from 0.03% to 0.45% [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if the clinician does not suspect this rare condition in the differential diagnosis and does not warn the pathologist, making a histopathological diagnosis might be problematic. At least two of the endometrial stroma, endometrial-like glands and hemosiderin pigments must be looked for during the pathological examination (13) ; however, if the pathologist is not informed about this differential diagnosis in the absence of endometrial glands, the endometrial stroma and macrophages could be underdiagnosed. It has been reported in the literature that not cleaning the surgical site with saline after the surgery and the use of sutures or sponges contaminated with endometrial cells lead to the development of endometriosis on the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Presenting symptoms were noted to include abdominal mass, cyclical and non-cyclical pain with dysmenorrhea [3,4]. Although rather uncommon, endometriosis can occur in the postmenopausal (oestrogen-deprived) state [5], and usually occur in women who undergo unopposed oestrogen replacement therapy [6].…”
Section: Discussionmentioning
confidence: 99%